Sistem Penunjang Keputusan Penilaian Kinerja Karyawan Berprestasi Menggunakan Acuan MBO dan Metode AHP Menggunakan Aplikasi Expert Choice - Rudi Sutomo; Johny Hizkia Siringo Ringo (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
In the determination of employees who have the achievement required assessment of the assessment. There are several policy setting criteria to be able to prevent subjective decision-makers such as the influence of